Description of a new subspecies, Macrobrachium aemulum madhusoodani (Decapoda: Palaemonidae) from Neyyar River, Kerala, S. India - Pillai, P. M.; Unnikrishnan, V. (Zootaxa, 2013)
Macrobrachium aemulum madhusoodani, a new subspecies of M. aemulum (Nobili, 1906) is described and illustrated. The distinctive characters of the subspecies are: rostral formula 9–13/2, second pereiopods dissimilar in shape and unequal in size, movable finger of larger second pereiopod with 2 large denticles on the proximal part and 6 weak denticles on distal part. Similar pattern of dentition is present on immovable finger also. In second small pereiopod, fingers stout, equal, unarmed with distinct gap in between when closed. Numerous stiff setae present on cutting edges of fingers. Telson extends beyond the level of the outer lateral spine of the uropodal exopod. Some of the distinctive morphometric and meristic characters of the specimens did not conform to that collected and described from New Caledonia by Nobili (1906) and recorded from India by Jayachandran and Joseph (1988). Since the features cannot be reckoned as mere growth variations, it is described herein as a new subspecies.